A utilização de tecnologias digitais no Curso de Licenciatura em Matemática PARFOR/EAD da Universidade Federal de Uberlândia - Gonçalves, Elivelton Henrique (2018)
This research focuses its efforts in the study of Digital Technologies (DTs) in the education of future Mathematics teachers by distance modality. The question that guided the research was: how are Digital Technologies methodologically approached by professors of undergraduate studies in Mathematics by distance modality at the Federal University of Uberlândia? Seeking an answer to this questioning, the following were proposed as objectives: (i) to analyze how the professors organized the teaching of their subjects addressing content related to DTs; and (ii) to analyze how DTs were approached in the diverse course subjects from the perspective of the undergraduate students in Mathematics and the tutors. The research had the undergraduate course in Mathematics by distance modality as context - part of the National Development Plan for Teachers of Basic Education (PARFOR) of the Federal University of Uberlândia, Brazil. By adopting the qualitative research approach, it started the investigation from two interrelated moments - the analysis of the Pedagogical Course Project and the analysis of the Virtual Learning Environment. Based on both settings, along with information from the online questionnaire proposed to the undergraduate students later, it was possible to identify eight disciplines that addressed DTs during the course. Subsequently, it performed two procedures to generate data: an interview with the professors who taught these courses and the proposal of an online questionnaire to the undergraduate students and tutors involved in the course / disciplines, with 4 professors, 15 undergraduates and 9 tutors participating. By means of exhaustive and repeated readings of the information produced in the research, we constructed four emerging categories of analysis: (i) the dynamics of the disciplines, (ii) the monitoring and evaluation of the undergraduates, (iii) the undergraduates’ participation, and (iv) DT approach in the course and the implication for teacher education. The results indicate professors’ diligence in their teaching organization; the professors developed proposals that aimed to stimulate the critical and conscious use of these resources by the undergraduate students to enable the future teachers to identify possibilities to integrate the apparatuses into teaching and learning situations. Regarding the undergraduates, the results demonstrate that they have acquired technical knowledge to handle the DTs. However, there are evidences showing their main difficulty to understand how to deal with the mathematical contents from the technologies approached. The tutors also indicated that scenario. Despite this, professors, undergraduate students, and tutors share the view that these disciplines were, above all, a groundwork that presented the DTs and aroused their alleged use in the school context, as well as the need for a permanent state of development and new pursuits. This research seems to highlight the importance of greater care and attention by the professors’ in organizing their disciplines. Proposing formative situations that not only present the technologies to the undergraduate students, but also enable these future teachers to know these technologies, to experience them as a formative instrument and object of study, and to build knowledge about their integration as teaching tools in the Mathematics classroom.